Old-growth forests in the Dinaric Alps of Bosnia-Herzegovina and Montenegro: a continental hot-spot for research and biodiversity - Motta, Renzo; Alberti, Giorgio; Ascoli, Davide; Berretti, Roberta; Bilic, Srdjan; Bono, Alessia; Milic, Curovic; Vojislav, Dukić; Finsinger, Walter; Garbarino, Matteo; Govedar, Zoran; Keren, Srdjan; et al. (Frontiers in Forests and Global Change, 2024)
Introduction According to various censuses, Europe has less than 1.5 million ha of old-growth forests (OGF). Most of them are in the boreal zone, while their presence in the temperate zone is residual and fragmented.In the framework of the EU biodiversity strategy, it has been adopted a broad definition of OGF which includes late-seral forests and forests with some management legacies. However, research purposes need to identify strictly defined OGFs characterized by structure, disturbance history, and processes typical and exclusive of the last stage of the forest dynamic. Methods The present paper wants to contribute to this debate by presenting a research network of four mixed (Fagus-Abies-Picea) montane OGFs in the Dinaric Alps (Lom, BiH; Janj, BiH; Perućica, BiH; Biogradska Gora, MNE), summarizing 20 years of multidisciplinary research by focusing on the structural characteristics and the disturbance history of the whole network and their coherency with strict OGF indicators. These sites were selected in relatively structurally uniform study areas, where 142 permanent plots have been established since 2002. Results and discussion The study sites have a high living (747–1,201 m3 ha−1) and coarse woody debris (CWD) biomass (304–410 m3 ha−1), resulting in the highest forest carbon sink at the continental level (398–484 Mg C ha−1). The presence of large and old trees is one of the critical characteristics of the old-growth stage: in Lom and Perućica, there are 19 trees and 14 ha−1 larger than 1 m at breast height, respectively, and 14 trees and 15 trees ha−1 older than 400 years. In the last three centuries, continuous small-scale disturbances have driven forest dynamics, developing stands characterized by gap-phase dynamics and quasi-equilibrium structure. The Dinaric OGF network presents robust indicators of old-growthness, similar structural characteristics, and dynamic processes across all four sites. Identifying this sub-set of OGF using strict criteria is critical for recognizing conservation priorities and for quantifying, along an old-growthness chronosequence, the current structural differences of managed or recently abandoned forests. Besides, only OGF selected with rigorous criteria can act as a reliable reference for ecological restoration and sustainable forest management as a benchmark for carbon sink and for quantifying the impact of climate change on forests.